Evaluation of efficacy of laparoscopy in patients with chronic abdominal pain - Prasad, Sanjay; Jain, Suraj; Prakash, Advait; Gautam, Ajeet; Gadodia, Mohan; Gupta, Anand; Somani, Kiran (International Surgery Journal, 2017)
Background: Chronic abdominal pain is a major cause of surgical dilemma. Patients with chronic abdominal pain usually undergo a battery of investigations without yielding much in diagnosis. The pain in such patients therefore becomes chronic and perpetual source of discomfort. This study was under taken to assess the efficacy of performing diagnostic and therapeutic laparoscopy in patients with chronic abdominal pain for longer than 3 weeks or more. Methods: This prospective study was performed at a tertiary care level hospital. All patients undergoing laparoscopy for chronic abdominal pain were included in the study from December 2013 to June 2015. The patient’s demographic data, duration of pain, diagnostic studies, intra-operative findings during laparoscopy, interventions performed and follow-up were recorded and evaluated. Results: A total of 50 patients, 22 females and 28 males, between age range of 10 years to 60 years underwent diagnostic laparoscopy for the evaluation and treatment of chronic abdominal pain. The average duration with pain was 10.38 weeks (range 4-32 weeks). Findings included abdomen chronic appendicitis in 15 patients, abdominal tuberculosis in 11 patients, ovarian cyst five patients, sub acute intestinal obstruction in five patients and liver abscess four patients. Meckel’s diverticulum, ectopic pregnancy, pelvic abscess, appendicular lump, Psoas abscess and typhilitis were noted in one patient each. Various procedures in accordance with pathology were performed. 92% of patients had pain relief at the time of follow up. Conclusions: Diagnostic laparoscopy is a better, cost-effective, and efficient method of establishing the diagnosis in patients with chronic abdominal pain.